Association between Mycobacterium avium complex lung disease and serum vitamin D status, antimicrobial peptide levels, and bone mineral density. Issue 38 (September 2018) - Fujita, Kohei; Ito, Yutaka; Oguma, Tsuyoshi; Mio, Tadashi; Niimi, Akio; Hirai, Toyohiro
Abstract : Abstract: Vitamin D maintains calcium balance and has immunomodulatory effects. Only few studies have revealed the relationship between vitamin D and its associated factors in Mycobacterium avium complex (MAC) infection. This study aimed to investigate the effects of MAC infection on serum vitamin D, human cationic antimicrobial protein 18, its C-terminal 37 amino acid fragment (hCAP18/LL-37) levels, and bone mineral density (BMD). We enrolled 58 patients with MAC lung disease and 15 control participants. Serum 25-hydroxyvitamin D and hCAP18/LL-37 levels were measured via enzyme-linked immunosorbent assay. Lastly, computed tomography scan density readings of the BMD of the thoracic and lumbar vertebral bones (Th4, Th7, Th10, and L1) were assessed. No significant differences in patient characteristics and serum vitamin D levels were observed. Patients with MAC lung disease had significantly low serum hCAP18/LL-37 levels ( P = .049). Moreover, low BMD of the mean thoracic and lumbar vertebrae was observed (mean Th, P = .012; L1, P = .48, respectively). A higher prevalence of scoliosis ( P = .031) was observed in the participants with low BMD compared with the control participants. Based on a multivariate analysis, patients with MAC lung disease had significantly lower body mass index [odds ratio (OR), 19.1; 95% confidence interval (CI), 2.0–419.0; P < .01] and vertebral BMD (OR, 12.4; 95% CI, 1.7–160.6; P = .012) than control participants. Serum hCAP18/LL-37 level and BMD were significantly decreased in patients with MAC lung disease without relation to serum vitamin D level. The vitamin D–independent pathway might affect the waning of antimicrobial peptides and decrease in BMD.